PHYSICOCHEMICAL AND MICROBIAL ANALYSIS OF FECES FROM HORSES FED DIETS CONTAINING CITRUS PULP - Brandi, Roberta Ariboni (2016)
Abstract This study aimed to evaluate the effect of diets containing increasing levels of citrus pulp on the physicochemical and microbiological characteristics of horses feces. Five mares, at an average age of 3.5 years old and body weight of 492 ± 44.5 kg were arranged in a 5 x 5 Latin Square. The experimental diet consisted of 60% coast-cross hay and 40 % of concentrate with increasing levels of citrus pulp (0, 7, 14, 21, and 28 %). To determine the fecal pH, samples were collected directly from the floor, immediately after defecation, in the first feces of the day at 07:00 a.m., and color and fecal consistency were evaluated. For microbiological analysis, an aliquot was reserved in plastic bags, frozen, and sent to the microbiological laboratory for further analysis. Lactic acid bacteria were counted for Lactobacillus spp. and Streptococcus spp. from fecal samples under anaerobic conditions. The diet produced differences (P<0.05) in feces consistency: 98% of the animals had normal and firm stools, while 2% were loose ruminant-type feces. We observed no difference (P<0.05) for color, verifying 100% of the animals of greenish feces, normal for equines. There was no effect (P>0.05) on pH and on the number of Lactobacillus spp. and Streptococcus spp. The inclusion of up to 28% citrus pulp concentrates for horses did not promote change in the physicochemical characteristics and on the population of lactic acid-producing bacteria in feces.